The Effect of Peer Feedback on Students’ Writing - Rosi Anjarwati (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2017)
Writing is one of productive skill which frequently represents students’ ability in expressing their thought toward something. Peer-feedback is considered to be important point in students’ writing process. This article aims to investigate the effect of peer feedback on students’ writing achievement at STKIP PGRI Jombang. Quasi-experimental is used as research design with test as the main instrument and questionnaire as the secondary instrument. The result of ANCOVA showed that there is a significant effect of peer feedback on students’ writing achievement. Moreover, the result of students’ response toward the used of peer feedback indicates positive result